Feminism: When the Label ‘White’ Gets Attached in Pop Music Industry - Lee, Audrey; Oh, Brian Junsung (Columbia Undergraduate Research Journal, 2020)
This paper describes a qualitative study that investigates the pop music genre starting from the 2000s, relating it to feminism. The investigation focuses on understanding when female artists are considered feminist, and when the label ‘white feminist’ is applied to specific female artists. Based on media press and public perspective, the research hopes to find key characteristics that separates the moment when the label feminism and white feminism are applied, especially in relation to other attributes such as gender orientation, sexual orientation, and race. The purpose of the research is to provide more insight into understanding feminism in the context of today, and to how navigate complex spaces such as media image and personal identity, labels that come with the public status of their profession.